2011
DOI: 10.1093/cercor/bhr286
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Neural Substrates for Semantic Knowledge and Naming in the Temporoparietal Network

Abstract: Patients with anterior temporal lobe (ATL) lesions show semantic and lexical retrieval deficits, and the differential role of this area in the 2 processes is debated. Functional neuroimaging in healthy individuals has not clarified the matter because semantic and lexical processes usually occur simultaneously and automatically. Furthermore, the ATL is a region challenging for functional magnetic resonance imaging (fMRI) due to susceptibility artifacts, especially at high fields. In this study, we established a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 82 publications
4
44
1
Order By: Relevance
“…The central insula peaks in our study were most near regions associated with somatosensory and chemical perception (taste and smell) according to the Kurth meta-analysis (31), suggesting that access to representations of sensory experiences may have played a role in the ability to discriminate among emotions, and specifically to discern disgusted expressions in others. The role of the amygdala in emotional signal detection is well-established (45; 46), and the temporal regions found in our study have been widely associated with both socioemotional (R>L) and object-related (L>R) semantic knowledge (47; 48) as well as the ability to access the lexical names of emotions (4952). …”
Section: Discussionsupporting
confidence: 54%
“…The central insula peaks in our study were most near regions associated with somatosensory and chemical perception (taste and smell) according to the Kurth meta-analysis (31), suggesting that access to representations of sensory experiences may have played a role in the ability to discriminate among emotions, and specifically to discern disgusted expressions in others. The role of the amygdala in emotional signal detection is well-established (45; 46), and the temporal regions found in our study have been widely associated with both socioemotional (R>L) and object-related (L>R) semantic knowledge (47; 48) as well as the ability to access the lexical names of emotions (4952). …”
Section: Discussionsupporting
confidence: 54%
“…Naming involves a series of processing stages including conceptual processing, word selection, phonological retrieval, phonological encoding and articulation 48 , and hence relies on numerous brain regions and is vulnerable in all types of aphasia 9 . The mid temporal and posterior temporal regions we identified may be relatively more involved in word selection and phonological retrieval respectively 32,39,66 . Previous studies have reported associations between naming deficits and damage to a range of left temporal regions in post-stroke aphasia 5,20,22,25,37,66 .…”
Section: Discussionmentioning
confidence: 81%
“…However, the fMRI meta-analysis of Rice, Lambon Ralph, et al (2015) challenges this assertion by demonstrating that semantic processing of non-verbal stimuli engages the rostral temporal cortex bilaterally. fMRI studies of famous face processing also reveal bilateral activation, even when name retrieval is controlled for (Brambati, Benoit, Monetta, Belleville, & Joubert, 2010; Gesierich et al, 2011; Gorno-Tempini et al, 1998; Von Der Heide, Skipper, & Olson, 2013). Another possibility is that the right-lateralized regions are more important for social behaviors because of greater connectivity to high-level social regions in the frontal lobe via the uncinate fasciculus (Highley, Walker, Esiri, Crow, & Harrison, 2002; Papinutto et al, 2016; Von Der Heide, Skipper, Klobusicky, & Olson, 2013).…”
Section: Discussionmentioning
confidence: 96%